Peran Kesultanan Deli dalam Pengembangan Islam di Medan - Abdul Gani Jamora Nasution; Irlyanova Sabina; Khoiriah Marta Parapat; Rizki Ramadhani (YASIN, 2023)
Islam entered Indonesia in the 7th or 8th century, and there are two routes for the entry of Islam into Indonesia, namely, the northern route with the route: Arabia (Mecca and Medina). Damascus, Iraq. Persia, Gujarat (West coast of India), Sri Lanka and Indonesia. And the South route with the Arab route (Mecca and Medina). Yemen, Gujarat, Sri Lanka and Indonesia. The development of Islam in Indonesia is through a process of dissemination that accommodates local cultures so as to form an Indonesian-style Islamic tradition. From these developments a new kingdom was born in Medan, namely the Deli Sultanate with the culture of the Malay community. The Sultanate of Deli and its people have produced a great civilization, which in Old Malay is usually called tamadun. The purpose of this study was to find out what the contribution or role of the Sultanate of Deli was in the development of Islam in Medan. This research was conducted using a historical study approach. The results showed that Sultan Makmun Alrasyid contributed more to the contribution of the Sultanate of Deli, such as he who had built the Maimun Palace and several mosques in Negeri Deli.